Differential Expression of Platelet Glycoprotein Ia/IIa in Taiwan Chinese Corresponds to Glycoprotein Ia Gene Polymorphisms - Liu Chao-Zong; Wang Yi-Chai; Wang Ji-Hung; Shaw Cheng-Kuang; Lin Gang-Ling (Elsevier, 2006)
Abstract.: Glycoprotein (GP) Ia/IIa plays a key role in platelet function by acting as a primary receptor for subendothelial collagen, thereby contributing to arterial thrombosis. In this study, we found that the expression level of platelet GPIa/IIa among Taiwan Chinese varies over sixfold and this difference relates either to the GPIa gene 807 C/T dimorphisms or the appearance of BglII restriction sequence within intron G. This is the first study to demonstrate the wide variation of platelet GPIa/IIa density in an Oriental population and its correlation to the GPIa gene polymorphisms. These results provide useful tools for predicting platelet GPIa/IIa density of Chinese. Keywords:: collagen, glycoprotein Ia/IIa density, glycoprotein Ia gene polymorphism